Nonelective surgery at night and in-hospital mortality: Prospective observational data from the European Surgical Outcomes Study. Issue 7 (July 2015) - van Zaane, Bas; van Klei, Wilton A.; Buhre, Wolfgang F.; Bauer, Peter; Boerma, E. Christiaan; Hoeft, Andreas; Metnitz, Philipp; Moreno, Rui P.; Pearse, Rupert; Pelosi, Paolo; Sander, Michael; Vallet, Benoit; et al.
Abstract : BACKGROUND: Evidence suggests that sleep deprivation associated with night-time working may adversely affect performance resulting in a reduction in the safety of surgery and anaesthesia. OBJECTIVE: Our primary objective was to evaluate an association between nonelective night-time surgery and in-hospital mortality. We hypothesised that urgent surgery performed during the night was associated with higher in-hospital mortality and also an increase in the duration of hospital stay and the number of admissions to critical care. DESIGN: A prospective cohort study. This is a secondary analysis of a large database related to perioperative care and outcome (European Surgical Outcome Study). SETTING: Four hundred and ninety-eight hospitals in 28 European countries. PATIENTS: Men and women older than 16 years who underwent nonelective, noncardiac surgery were included according to time of the procedure. INTERVENTION: None. MAIN OUTCOME MEASURES: Primary outcome was in-hospital mortality; the secondary outcome was the duration of hospital stay and critical care admission. RESULTS: Eleven thousand two hundred and ninety patients undergoing urgent surgery were included in the analysis with 636 in-hospital deaths (5.6%). Crude mortality odds ratios (ORs) increased sequentially from daytime [426 deaths (5.3%)] to evening [150 deaths (6.0%), OR 1.14; 95% confidence interval 0.94 to 1.38] to night-time [60 deaths (8.3%), OR 1.62; 95% confidence interval 1.22 to 2.14]. Following adjustment for confounding factors, surgery during the evening (OR 1.09; 95% confidence interval 0.91 to 1.31) and night (OR 1.20; 95% confidence interval 0.9 to 1.6) was not associated with an increased risk of postoperative death. Admittance rate to an ICU increased sequentially from daytime [891 (11.1%)], to evening [347 (13.8%)] to night time [149 (20.6%)]. CONCLUSION: In patients undergoing nonelective urgent noncardiac surgery, in-hospital mortality was associated with well known risk factors related to patients and surgery, but we did not identify any relationship with the time of day at which the procedure was performed. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT01203605 Abstract : Supplemental Digital Content is available in the text